2016
DOI: 10.1128/jvi.01347-16
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Polyamine Biosynthesis Is a Broad-Spectrum Strategy against RNA Viruses

Abstract: RNA viruses present an extraordinary threat to human health, given their sudden and unpredictable appearance, the potential for rapid spread among the human population, and their ability to evolve resistance to antiviral therapies. The recent emergence of chikungunya virus, Zika virus, and Ebola virus highlights the struggles to contain outbreaks. A significant hurdle is the availability of antivirals to treat the infected or protect at-risk populations. While several compounds show promise in vitro and in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
114
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(118 citation statements)
references
References 31 publications
4
114
0
Order By: Relevance
“…Treatment of cells with DFMO significantly reduced viral titers, which were then rescued by replenishing polyamines exogenously (32,60,61). More recently, a report by Mounce et al expanded our knowledge of RNA viruses requiring polyamines for replication using DFMO depletion of cellular polyamines (62,63). The list of RNA viruses sensitive to polyamine depletion has been extended to include diverse families, including alphaviruses (chikungunya virus [CHIKV]), coronaviruses (Middle East respiratory syndrome [MERS] virus), enteroviruses (enterovirus A71 and poliovirus), flaviviruses (dengue virus serotype 1, Japanese encephalitis virus, and yellow fever virus), rhabdoviruses (rabies virus), and bunyaviruses (Rift Valley fever virus) (summarized in Table 1) (62,63).…”
Section: Polyamines In the Replication Of Rna Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of cells with DFMO significantly reduced viral titers, which were then rescued by replenishing polyamines exogenously (32,60,61). More recently, a report by Mounce et al expanded our knowledge of RNA viruses requiring polyamines for replication using DFMO depletion of cellular polyamines (62,63). The list of RNA viruses sensitive to polyamine depletion has been extended to include diverse families, including alphaviruses (chikungunya virus [CHIKV]), coronaviruses (Middle East respiratory syndrome [MERS] virus), enteroviruses (enterovirus A71 and poliovirus), flaviviruses (dengue virus serotype 1, Japanese encephalitis virus, and yellow fever virus), rhabdoviruses (rabies virus), and bunyaviruses (Rift Valley fever virus) (summarized in Table 1) (62,63).…”
Section: Polyamines In the Replication Of Rna Virusesmentioning
confidence: 99%
“…More recently, a report by Mounce et al expanded our knowledge of RNA viruses requiring polyamines for replication using DFMO depletion of cellular polyamines (62,63). The list of RNA viruses sensitive to polyamine depletion has been extended to include diverse families, including alphaviruses (chikungunya virus [CHIKV]), coronaviruses (Middle East respiratory syndrome [MERS] virus), enteroviruses (enterovirus A71 and poliovirus), flaviviruses (dengue virus serotype 1, Japanese encephalitis virus, and yellow fever virus), rhabdoviruses (rabies virus), and bunyaviruses (Rift Valley fever virus) (summarized in Table 1) (62,63). Replication of each of these viruses was impacted to various degrees when polyamines were depleted with DFMO and rescued when polyamines were replenished exogenously.…”
Section: Polyamines In the Replication Of Rna Virusesmentioning
confidence: 99%
“…Future studies are necessary to test these FDA approved drugs or clinical trial drug candidates in animal models for their efficacy as well as toxicity before moving to clinical trials. In addition to nonbiased large scale screens, studies based on mechanistic insights have also identified individual drugs and compounds that inhibit ZIKV replication and/or protect neural progenitors from cell death (Deng et al, 2016; Mounce et al, 2016; Onorati et al, 2016; Zmurko et al, 2016). Some of these compounds have been validated in animal models, but remain to be tested in the microcephaly model in vivo (Deng et al, 2016; Zmurko et al, 2016).…”
Section: Opportunities and Challenges For Zikv Research Using Stem Cellsmentioning
confidence: 99%
“…Difluoromethylornithine (DFMO, also eflornithine), a polyamine inhibitor, has been approved by the FDA to treat African trypanosomiasis and cancer [110,111]. DFMO has been shown to reduce viral production of MERS-CoV 30-fold in Vero cells [112]. DFMO needs to be further studied to clarify its in vivo toxicity and efficacy.…”
Section: Polyamine Biosynthesis Inhibitormentioning
confidence: 99%